1977
DOI: 10.1677/joe.0.0750059
|View full text |Cite
|
Sign up to set email alerts
|

Steroid and Prostaglandin Concentrations in the Plasma of Pregnant Ewes During Infusion of Adrenocorticotrophin or Dexamethasone to Intact or Hypophysectomized Foetuses

Abstract: Catheters were implanted into 16 ewes and their foetuses between days 110 and 124 of gestation. Hypophysectomy was attempted in eight of these foetuses. Continuous infusion of synthetic ACTH (10 microgram/h) or dexamethasone (1mg/24 h) into the foetus, starting between days 124 and 129, induced premature parturition. The concentration of progesterone in the maternal peripheral plasma decreased before parturition in all animals while the level of oestradiol increased in ewes with intact foetuses or in those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 9 publications
3
11
1
Order By: Relevance
“…These data agree with earlier reports (Flint et al, 1975 ;Kendall et al, 1977) and with infusion experiments using adrenocorticotropin (Kendall, et al, 1977 …”
supporting
confidence: 94%
See 2 more Smart Citations
“…These data agree with earlier reports (Flint et al, 1975 ;Kendall et al, 1977) and with infusion experiments using adrenocorticotropin (Kendall, et al, 1977 …”
supporting
confidence: 94%
“…This latter procedure momentarily inhibits cortisol secretion by the foetal adrenals and then stimulates it (Bosc and Fèvre, 1974). If the foetus has been hypophysectomized however, administration of cortisol to the mother does not induce delivery (Bosc, 1972) while perfusion into the foetus results in the birth of the lamb (Kendall et al, 1977 (Bosc, 1972 ; Bosc and Fèvre, 1975 Hormone assays : The steroids were assayed by radioimmunoassay. Progesterone was determined according to Palmer and Jousset (1975) with the following steps : plasma extraction (0,5 ml) with hexane (5 ml) ; after evaporation, addition of a phosphate-buffered solution containing tritiated progesterone and a specific antiserum (Yenikoye, 1977) fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the endocrine changes at parturition induced by the infusion of glucocorticoids and adrenocorticotrophin to the intact fetal lamb are similar to those at term , it has been suggested that the pre-partum rise in oestrogen level is not essential for parturition. This premise was based on the apparent absence of an increase in maternal plasma concentrations of oestrogen when parturition was induced by adrenocorticotrophin treatment of the hypophy¬ sectomized ovine fetus (Kendall et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a role for GH in glucocorticoid action in the fetus is uncertain because the late gestational induction of PRLR expression coincides with a fall in fetal plasma GH levels in humans as well as sheep (24). Interestingly, the administration of dexamethasone to fetal sheep near term increases the levels of 17-␤ estradiol in fetal blood (31), suggesting that estrogens may mediate some of the biological effects of glucocorticoids in the fetus. The aforementioned studies of the induction of GH and PRL receptors in the ovine fetus (5,6,19) did not examine the effects of adrenalectomy or cortisol administration on fetal estrogen levels.…”
mentioning
confidence: 99%